Factor V Leiden, C>T MTHFR Polymorphism and Genetic Susceptibility to Preeclampsia - Grandone, Elvira; Margaglione, Maurizio; Colaizzo, Donatella; Cappucci, Giuseppe; Paladini, Dario; Martinelli, Pasquale; Montanaro, Sergio; Pavone, G; Minno, Giovanni Di (Thrombosis and Haemostasis, 1997)
We performed a case-controlled study to investigate whether the FV Leiden mutation and the C>T677 polymorphism of the 5,10 methylene tetrahydrofolate reductase (MTHFR) are associated with the occurrence of preeclampsia in 96 otherwise healthy preeclamptic women and 129 parous women as controls. FV Leiden carriers were 10 (10.5%) in cases and 3 (2.3%) in controls (OR: 4.9, 95% Cl: 1.3-18.3). MTHFR TT homozygotes were 28 (29.8%) in cases and 24 (18.6%) in the control group (OR: 1.8,95% Cl 1.0-3.5). No difference in any of the polymorphisms was found between proteinuric (n = 45) and non-proteinur-ic (n = 51) patients. Moreover, MTHFR polymorphism does not affect the association between FV Leiden and preeclampsia. In conclusion, FV Leiden mutation and MTHFR TT genotype are associated with the occurrence of preeclampsia, suggesting that, during pregnancy, women carrying these gene variants are prone to develop such a complication.